PENINGKATAN PENJUALAN PRODUK BERBASIS PENDAMPINGAN PADA UMKM HAULA FROZEN FOOD DI DESA KEMIRI: ENHANCING PRODUCT SALES THROUGH MENTORSHIP AT HAULA FROZEN FOOD MSME IN KEMIRI VILLAGE - Laela Rahma Adila; Rabhi Fathan Muhammad (Jurnal Pengabdian Masyarakat Multidisiplin, 2025)
The Haula Frozen Food MSME in Kemiri Village, Karawang Regency, faces challenges in digital marketing, resulting in limited market reach and low sales volume. To address this issue, a assistance program was implemented to enhance the effectiveness of marketing and sales through digital-based strategies.This assistance program employed the Participatory Action Research (PAR) method, actively involving MSME actors in every stage of planning and implementation. The program included the creation of visual identity elements such as logos, brochures, and banners to strengthen brand image, as well as the development of Standard Operating Procedures (SOP) for E-Commerce. Additionally, MSMEs were guided in optimizing the use of digital platforms such as WhatsApp Business, TikTok Shop, and Shopee as marketing and sales channels.The results showed a significant increase in revenue by 62.5%, sales volume by 68.18%, a wider market reach, and improved brand awareness among consumers. The intensive assistance process ensured that MSME actors could independently manage their digital marketing strategies, thereby increasing business competitiveness in the digital era and supporting sustainable business growth.